PENERAPAN PEMBELAJARAN BERDIFERENSIASI MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS IV SD INPRES BERTINGKAT GOWA KABUPATEN GOWA - Annisa Dwi Puspita; Dewi Sartika (STKIP Subang, 2024)
This classroom action research aims to understand how differentiated learning is implemented in Grade IV and to improve learning outcomes on the topic of multiplication of whole numbers up to 100 in the Mathematics subject for Grade IV students at SD Inpres Bertingkat Gowa, Gowa Regency. The subjects of this research are 30 students from Grade IV of SD Inpres Bertingkat Gowa. Data collection methods included tests and observation. This classroom action research was conducted in 2 cycles. Each cycle involved planning, action, observation, and reflection phases. The reflection phase aimed to explore alternative strategies for improvement in the next stage. With the application of differentiated learning on figurative language material, there was an increase in students' learning outcomes because differentiated learning allows students to learn according to their preferences and abilities, aligning with their learning profiles, including visual, auditory, and kinesthetic learning styles. The improvement in student learning outcomes in the topic of multiplication of whole numbers up to 100 progressed from the pre-cycle to Cycle I, with the class average score increasing from 50.00 before the cycle to 75.00 in Cycle I, and further rising to 85.00 in Cycle II. The percentage of improvement in learning outcomes was 50% in Cycle I and increased to 70% in Cycle II.